There is no Target Oriented Speaking Activity without Motivation: Peculiarities of Children’s Monologues Expressions - Larysa Kalmykova; Iryna Volzhentseva; Nataliia Kharchenko; Іnna Мysаn (Психолінгвістика)
The aim of the article is in the description a) of finding out motivation peculiarities in extended monologue expressions and speech motives of the children of five and six years olds in ontogenesis; b) established connection between development state of speech motives and development state of lexical and grammatical expressions structuring that are out speaking and have great explanation strength while interpreting mastering and owing processes of the native language and oral speech. The used scientific methods are: а) theoretical (analyses of scientific resources, generalization of analyzed literature and its systematization, pointing out of some basic terms, which make the ground of the research, conclusion formulation); b) empirical (playing situations, motivating and speech screening, linguistic content-analyses of children’s judgments, stated, formatting and controlling experiments and survey of children; v) statistics methods. Study of children’s monologue expressions was done in terms of speech operations. The results of children’s speech observation uncover peculiarities and development levels of Ukrainian speaking children speech motives of five and six years, peculiarities of children’s speech motivation typical for every of pointed out levels which witnesses that every child who is developing due to the established criteria has individual and irregular development of motivating and speech operations and actions; highlight the dynamic, vectors and mechanisms of speech motivation development; demonstrate typical strategies of gaining by children meaning formulating motive concepts; gradual development of motive targets, with which appearance we see changing of motive and aim, and speech children’s activities epigenetically gain the status of self-estimated and sustainable and goal oriented speech activity; underline operation specific of grammatical structuring of the phrases and extended monologue expressions and selecting words operations according to the forms acted by children; confirm correlated analyses interconnections among motivating and lexically grammatical operations.